Tracing Hepatitis E Virus in Pigs From Birth to Slaughter - Krog, Jesper S.; Larsen, Lars E.; Breum, Solvej Ø. (Frontiers in Veterinary Science, 2019)
Pigs are considered the main reservoir of genotypes 3 and 4 of the human pathogen hepatitis E virus (HEV). These viruses are prevalent at a high level in swineherds globally, meaning that consumers may be exposed to HEV from the food chain if the virus is present in pigs at slaughter. The aim of this study was to determine the HEV infection dynamics from birth to slaughter using 104 pigs from 11 sows in a single production system. Serum was collected from sows at two weeks prior to farrowing, in addition feces and serum samples were collected from the pigs every second week, from week one to week seventeen. Feces and selected organs were also sampled from 10 pigs following slaughter at week 20. All the samples were tested for HEV RNA by real-time RT-PCR and the serum samples were tested for HEV-specific antibodies using a commercial ELISA. Maternal antibodies (MAbs) were only present in pigs from sows with high levels of antibodies and all pigs, except one, seroconverted to HEV during weeks 13-17. In total, 65.5 % of the pigs tested positive for HEV RNA at least once during the study (during weeks 13, 15 and/or 17) and significantly fewer pigs with a high level of MAbs became shedders. In contrast, the level of MAbs had no impact on the time of onset and duration of virus shedding. HEV was detected in feces and organs, but not in muscle, in 3 out of 10 pigs at slaughter, indicating that detection of HEV in feces is indicative of an HEV positivity in organs. In conclusion, a high proportion of pigs in a HEV positive herd were infected and shed virus during the finisher stage and some of the pigs also contained HEV RNA in feces and organs at slaughter. The presence of MAbs reduced the prevalence of HEV shedding animals, therefore, sow vaccination may be an option to decrease the prevalence of HEV positive animals at slaughter.